(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the psycholinguistic features of communication in Uzbek and English languages through literature review and theoretical analysis. The study examines linguistic, cognitive, and psychological aspects of communication processes in both languages, focusing on cross-cultural communication patterns and mental processing characteristics. The research is based on existing literature analysis and provides insights into cultural and psychological aspects of interlingual communication.